The Effectiveness of Educational Management in Reducing Inequality in Learning Access at Public Senior High Schools - Indarsih Rohani Rohani; Tri Yuni Hendrowati; Fatqul Hajar Aswad (Al-Qalam Institue, 2026)
This study aims to examine the effectiveness of educational administration management in addressing disparities in learning access by analyzing the key dimensions of educational management: planning, organizing, implementing, and evaluating. A qualitative case study approach was employed to gain an in-depth understanding of administrative practices. Data were collected through interviews with the principal, administrative staff, teachers, students, and parents, as well as through observations and document analysis. The data were analyzed using Miles and Huberman’s interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that in the planning dimension, the school utilizes data-driven tools such as Dapodik and RKAS to design inclusive programs. Organizational efforts include flexible task distribution to accommodate diverse student needs. Implementation is responsive, addressing individual student requirements, though documentation practices are inconsistent. Evaluation remains sporadic and has not yet developed into a structured, sustainable monitoring system. These findings underscore the need for a more systematic, data-informed, and participatory approach to educational administration. Strengthening administrative staff capacity, developing adaptive policies, and establishing ongoing monitoring systems are recommended to enhance service effectiveness and ensure equitable access to education.